Histomorphological features of Rabbit Uterine Tube During Estrous Phases - Samira Abdul-Hussein Abdullah (Tikrit Journal of Pure Science, 2019)
Microscopic features of the adult rabbit uterine tube during estrous cycle were studied. Twenty rabbit uterine tube were used. Rabbits were collected from local market. Sections from uterine tube infundibulum, ampulla and isthmus were prepared for histological study. Lengths and widths of various parts were obtained from the right tube.